Inovasi bahan ajar aljabar berbasis pendekatan saintifik berbantuan canva untuk meningkatkan kemampuan pemahaman matematis siswa SMP - Kholifah Nur Rosydah; Nelly Fitriani; Ika Wahyu Anita (IKIP Siliwangi, 2026)
This study aimed to develop a Canva assisted student worksheet (LKPD) based on the scientific approach that was valid, practical, and effective in improving junior high school students’ mathematical understanding of algebra. The study employed the ADDIE development model. The participants consisted of 30 junior high school students in West Bandung Regency. Data were collected through a pretest and posttest consisting of five algebra questions, questionnaires, interviews, and media validation. The data were analyzed using the normalized gain (N Gain) test. The results showed that the feasibility of the Canva assisted scientific approach based LKPD was categorized as very feasible. The N Gain analysis produced an average score in the high category with an effectiveness percentage classified as effective. These findings indicated that the Canva assisted scientific approach based LKPD was feasible and effective in improving junior high school students’ understanding of algebra.